PENGEMBANGAN POTENSI DIRI SISWA MELALUI INTEGRASI KURIKULUM MERDEKA BELAJAR DAN TEKNOLOGI DIGITAL SEBAGAI UPAYA MENYIAPKAN GENERASI TANGGAP SOCIETY 5.0 - Al-Amin; Irda Suriani (JOURNAL OF COMMUNITY DEDICATION, 2025)
This study aims to examine the role of the integration of the Merdeka Belajar Curriculum and digital technology in developing students' self-potential as an effort to prepare a generation that is responsive to Society 5.0. Through a literature review method, this study examines various scientific references and educational policies related to the implementation of the Merdeka Curriculum, the use of digital technology in learning, and the concept of Society 5.0. The results of the study indicate that the integration of both is capable of creating a more flexible, contextual, and learner-centred learning ecosystem. The implementation of the Merdeka Curriculum, which is project-based and differentiated, supported by digital technology, promotes the strengthening of 21st-century competencies such as critical thinking, creativity, communication, collaboration, and digital literacy. However, several challenges remain, including technological access gaps, educator readiness, and the need for continuous training. Therefore, multi-stakeholder collaboration is essential to optimise the development of students' potential. This integration represents a strategic step in shaping a generation that is not only academically excellent but also adaptive, resilient, and prepared to tackle the complex challenges of the global Society 5.0 era.